#31: Children with Invasive S. aureus Infection Produce Broadly Neutralizing Antibodies Against Distantly Related Variants of the Cytotoxin LukAB. (28th June 2021) - Bennett, Monique; Kose, Nurgun; Perelman, Sofya; Crowe, James; Torres, Victor; Thomsen, Isaac
Abstract: Background: Staphylococcus aureus is the most common invasive bacterial pathogen in children, and novel targets of intervention are urgently needed. The two-component leukotoxin, LukAB, is critical for S. aureus targeting and killing of human neutrophils and is abundantly produced in the setting of invasive human infection. LukAB is unique among S. aureus cytotoxins in that it exists in variant form across distantly related strains of clinically relevant S. aureus . The broad diversity of circulating clinical S. aureus strains must be taken into account to successfully develop new anti-staphylococcal preventives or therapeutics. This diversity and ongoing S. aureus evolution may explain previous unsuccessful attempts to intervene against S. aureus at the virulence factor level. We have previously shown that LukAB is ubiquitous among clinical isolates and that children with invasive disease mount a high-titer neutralizing response, but the breadth of function of this response has not previously been explored. Methods: B-cells were isolated from children with invasive S. aureus infections (e.g. bacteremia or acute hematogenous osteomyelitis). Following EBV-transformation, cell supernatants were screened for LukAB binding and selected for generation of monoclonal hybridomas. MAbs were assessed for binding by ELISA and neutralizing function by in vitro cytotoxicity assays, where neutrophil-like HL-60 cells were cultured in the presence of human mAbs and diverse allelic variants of LukAB. The infecting S. aureus isolates were typed using multilocus sequence typing (MLST) to determine clonal complexes. Results: 34 distinct human anti-LukAB mAbs were generated from 3 children with invasive S. aureus disease. Of these, 22% were isolated following infection with a strain belonging to clonal complex 8 (CC8), consistent with the epidemic USA300 clone, and 78% were generated against CC5 strains. Within this panel, all mAbs potently neutralized LukAB from the same clonal complex as the corresponding infecting isolate, but 23 also demonstrated neutralization against other allelic variants of LukAB. 7 mAbs were capable of broad, potent neutralization against LukAB variants from all clinically relevant clonal complexes tested (CC8, CC30, CC45, CC75, CC1, CC5, and CC398). Conclusions: A subset of human mAbs isolated from children with invasive S. aureus disease were capable of broad neutralization against distantly related variants of the important toxin LukAB. This has two important implications: First, we found strong evidence of a conserved target (or targets) for antibody-mediated toxin neutralization across diverse strains of S. aureus . Second, this provides additional support for this toxin as a target of intervention, as some previous vaccine attempts were likely unsuccessful due to activity against a narrow subset of circulating S. aureus strains.